The Effect Of The Project Based Learning Model On Creativity And Indonesian Language Learning Outcomes Of Grade V Elementary School Students In Poigar District - Atalya Cherin Dwi Hamber; Mersty E. Rindengan; Mayske R. Liando (PT. AHLAL PUBLISHER NUSANTARA, 2026)
This study aims to analyze the effect of the project-based learning model on creativity and Indonesian language learning outcomes, especially in fiction and non-fiction stories of fifth-grade elementary school students in Poigar District. This study is based on the low creativity and learning outcomes of students caused by learning that is still centered on elementary school teachers and the lack of use of innovative learning models. This study uses a quantitative approach with a quasi-experimental method (equation experiment) and a non-equivalent group design. The study population was 40 fifth-grade students consisting of two schools, namely SDN 1 Poigar and SDN 1 Nanasi. The research sample was taken using a purposive sampling technique with 20 students as the experimental class and 20 students as the control class. Data collection techniques used tests, questionnaires, and observations. The research instrument has been tested for validity and reliability with the results of all items declared valid and reliable. Data analysis was carried out through normality tests, homogeneity tests, and hypothesis testing using independent sample t-tests. The results showed that there was a significant influence of the use of the project-based learning model on student creativity and learning outcomes. This is evidenced by a significance value (2-tailed) of 0.001 < 0.05. In addition, the implementation of the PjBL model can increase students' active involvement, creative thinking skills, and learning outcomes in writing fiction and non-fiction stories. Based on the research results, it can be concluded that the project-based learning model is effective in improving creativity and Indonesian language learning outcomes of fifth-grade elementary school students. Therefore, this model is recommended to be implemented as an alternative innovative learning to improve the quality of learning. Keywords: Project Based Learning, Creativity, Learning Outcomes, Indonesian